Early Jurassic Rare Metal Granitic Pluton of the Central Asian Orogenic Belt in North-Central Mongolia: Tungsten Mineralization, Geochronology, Petrogenesis and Tectonic Implications - Dostal, Jaroslav; Svojtka, Martin; Gerel, Ochir; Corney, Randolph (Frontiers in Earth Science, 2020)
The Tukhum granitic pluton is a part of the Mesozoic composite Khentei batholith of north-central Mongolia, which belongs the Central Asian Orogenic Belt. The shallow-seated pluton (~900 km2) is made up of two distinct biotite granite intrusions dated at ~ 191 and 183 Ma and hosts a tungsten deposit associated with the younger phase. Both intrusions are composed of ferroan A2- type granites, which are fractionated and silica-rich (> 71 wt.%). Their mantle-normalized plots are relatively enriched in Cs, Rb, U and Th and depleted in Ba, Sr, Eu, Nb and Ti. They have ƐNd(t) ranging from ~ 0 to +1 and Nd model ages ~ 650-900 Ma. The granites were derived by partial melting of a Neoproterozoic middle/lower crustal source of felsic/intermediate composition, followed by fractional crystallization. The younger intrusion also contains leucogranites with a trace element composition indicative of a combined crystal and fluid fractionation. The source of this younger intrusion was enriched in rare metals (W, Sn). The tungsten deposit is associated with the last stages of the evolution of the granitic magma. The origin of the pluton as well as the Khentei batholith is related to a mantle plume, which provided the heat triggering a crustal melting. The plume resulted in the eastward movement of large scale magmatism over time, from the Tarim traps (300-275 Ma) through the large Khangai magmatic centre (270-240 Ma) to the Khentei batholith (230-180 Ma) in north-central Mongolia.